Evaluation of the suchey–brooks method of age estimation in an Australian subpopulation using computed tomography of the pubic symphyseal surface. Issue 3 (3rd January 2013) - Lottering, Nicolene; MacGregor, Donna M.; Meredith, Matthew; Alston, Clair L.; Gregory, Laura S.
Abstract Despite the prominent use of the Suchey–Brooks (S–B) method of age estimation in forensic anthropological practice, it is subject to intrinsic limitations, with reports of differential interpopulation error rates between geographical locations. This study assessed the accuracy of the S–B method to a contemporary adult population in Queensland, Australia and provides robust age parameters calibrated for our population. Three‐dimensional surface reconstructions were generated from computed tomography scans of the pubic symphysis of male and female Caucasian individuals aged 15–70 years (n = 195) in Amira® and Rapidform®. Error was analyzed on the basis of bias, inaccuracy and percentage correct classification for left and right symphyseal surfaces. Application of transition analysis and Chi‐square statistics demonstrated 63.9 and 69.7% correct age classification associated with the left symphyseal surface of Australian males and females, respectively, using the S–B method. Using Bayesian statistics, probability density distributions for each S–B phase were calculated, providing refined age parameters for our population. Mean inaccuracies of 6.77 (±2.76) and 8.28 (±4.41) years were reported for the left surfaces of males and females, respectively; with positive biases for younger individuals (<55 years) and negative biases in older individuals. Significant sexual dimorphism in the application of the S–B method was observed; and asymmetry in phase classification of the pubic symphysis was a frequent phenomenon. These results recommend that the S–B method should be applied with caution in medico‐legal death investigations of Queensland skeletal remains and warrant further investigation of reliable age estimation techniques. Am J Phys Anthropol, 2013. © 2013 Wiley Periodicals, Inc.